Bose–Einstein condensation in helium white dwarf stars. I - Mosquera, Mercedes Elisa (2010)
The formation of a Bose–Einstein condensate in the interior of helium white dwarfs stars is discussed. Following the proposal made by Gabadadze and Rosen, we have explored the consequences of such a mechanism by calculating the cooling time of the stars. We have found that it is shorter than the value predicted by the standard model.